Labor supply when tax evasion is an option - Øystein Jørgensen; Tone Ognedal; Steinar Strøm (University of Oslo, Department of Economics, 2005)
We estimate labor supply when tax evasion is an option, using a discrete choice model on pooled Norwegian survey data from 1980 and 2001. Direct labor supply elasticities, conditional on sectors, are in the range of 0.2-0.4. The elasticities are higher for work that is not registered for taxation, than for registered work. Overall wage increases have a positive impact on the supply of registered work and a negative impact on supply of unregistered work. In addition to economic factors such as wages and tax rates, also social norms and opportunities for tax evasion at the work place have an impact on the supply of unregistered labor. The model is used to simulate the impact on labor supply of changes in the tax structure, such as the lowering of marginal tax rates. The fraction of the population who did unreported work was reduced from 1980 to 2001. Lower and less progressive tax rates after 1980 have contributed to this reduction. Although taxes matter for supply of both reported and non-reported labor, the impact is not strong. Social norms and opportunities for tax evasion at the work place are also important in explaining the change.
Keywords: C25; D12; D81; H26; J22; 330; Labor supply; tax evasion; survey data; microeconometrics; Arbeitsangebot; Steuervermeidung; Mikroökonometrie; Schätzung; Norwegen